Analisis Wacana Kritis Model Teun A. Van Dijk terhadap Gaya Bahasa Pidato Presiden Prabowo Subianto pada Pekan Nasional Petani dan Nelayan ke-17 Tahun 2026 - Rika Erliani Harahap; Liliana Muliastuti; Siti Ansoriyah; Lia Marliana (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study aims to analyze the language style employed by President Prabowo Subianto in his speech delivered at the 17th National Farmers and Fishermen Week in 2026 using Teun A. Van Dijk's Critical Discourse Analysis framework. The study employed a qualitative approach with documentation techniques applied to the official speech transcript. Data were analyzed through Van Dijk's three analytical dimensions, namely text, social cognition, and social context. The findings reveal that, at the textual level, the speech is dominated by themes of support for farmers and fishermen as strategic actors in national development and food security. At the superstructure level, the speech is organized argumentatively through personal experiences, policy explanations, and reaffirmation of governmental commitments. At the microstructure level, the speech demonstrates the use of informal language, rhetorical strategies, repetition, and lexical choices that strengthen the relationship between the speaker and the audience. In terms of social cognition, the findings indicate the speaker's awareness of the media's role in shaping public opinion, as reflected in several instances of meta-communication. Meanwhile, the social context dimension reveals representations of power relations through the construction of social groups positioned either as supporters or obstacles to national interests. These findings suggest that the speech functions not only as a means of political communication but also as a medium for constructing ideology, legitimizing power, and shaping political identity. This study reinforces the view that language plays a significant role in representing social realities and power relations within society.